2002
DOI: 10.1080/0036554021000026934
|View full text |Cite
|
Sign up to set email alerts
|

ICU-acquired Nosocomial Infection: Impact of Delay of Adequate Antibiotic Treatment

Abstract: In order to measure the impact on survival of the early introduction of adequate antibiotic treatment for nosocomial bacteremia and pneumonia, a retrospective, cohort study was carried out over a period of 17 months in a 6-bed respiratory ICU. All patients presenting with a first episode of ICU-acquired nosocomial bacteremic infection (Centers for Disease Control criteria) or pneumonia [BAL culture > or = 10(4) colony-forming units (CFU)/ml or protected specimen brush culture > or = 10(3) CFU/ml] were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…This may also be true for admission APACHE II score, which was not a risk factor for VAP in our study although severity of illness is often reported as a risk factor for VAP. Prompt treatment with appropriate broad-spectrum antibiotics in ICU patients with clinical signs of infection is a general accepted strategy, and does improve survival [10,14,16,26,27]. However, such treatment may reduce the chance to obtain a positive microbiological culture despite infection and thus may lead to an under-diagnosis of pneumonia [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may also be true for admission APACHE II score, which was not a risk factor for VAP in our study although severity of illness is often reported as a risk factor for VAP. Prompt treatment with appropriate broad-spectrum antibiotics in ICU patients with clinical signs of infection is a general accepted strategy, and does improve survival [10,14,16,26,27]. However, such treatment may reduce the chance to obtain a positive microbiological culture despite infection and thus may lead to an under-diagnosis of pneumonia [7].…”
Section: Discussionmentioning
confidence: 99%
“…In patients without VAP, the mortality was about half, but the 2 groups were not matched for severity of disease or comorbidities. A further confounder is that inadequate empiric antibiotics to patients with VAP will increase mortality [10,14,16,26,27], and the attributable mortality would be smaller with good standard of care including liberal bronchoscopic cultures and proper use of antibiotics. Patients with trauma had an increased risk of developing VAP but not to die within 28 d. Trauma patients are usually previously healthy and the median age was lower before admittance (43 y compared to 60 y for nontrauma patients), which may explain a more favourable outcome for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these pathogens frequently cause disease in severely debilitated or immunocompromised patients [75]. Thus, mortality rates of NGB infections are generally high and the rapid introduction of appropriate empirical antimicrobial therapy remains crucial to improve clinical outcomes [3,5,10,69].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, susceptibility testing methodologies are not standardised for most of these organisms, especially routine or automated commercial tests used in clinical microbiology laboratories, although some standard-defining organisations are actively seeking validated standardised methods [NC-CLS, 2005]. Thus, the knowledge of their epidemiology and antimicrobial susceptibility patterns is necessary to allow the development of empirical therapeutic strategies [10].…”
Section: Introductionmentioning
confidence: 99%
“…Patients receiving delayed IV antibiotic treatment had greater hospital mortality compared with patients without the delay (70% versus 29%). Another study of 25 patients [199], observed that mortality increased if adequate antibiotic treatment was started after the first 24 h after diagnosis. After adjusting for the number of organ failures, the length of time without adequate antibiotic treatment remained associated with mortality.…”
Section: B Delay In Initiation Of IV Antibioticsmentioning
confidence: 97%